Simulation-based Multiple Automated Guided Vehicles Considering Charging and Collision-free Requirements in Automatic Warehouse - Lee, C. K. M.; Keung, K. L.; Ng, K. K. H.; Lai, Daniel C. P. (2018 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2018)
The deployment of automated guided vehicles in the automated warehouse has a great impact on the capacity in handling logistics activities. Simulation offers practical feedback and analytical solution at a designing stage of engineering applications. As for automated warehouse system, the optimal set of the combination of automated guided vehicles and workstations are highly depended on the size, dimensions, layout structure of the warehouse and working process. In this paper, the operations in the automatic warehouse were simulated to determine possible scenarios of the warehouse setting regarding the demand pattern of the packaging order. In the automatic warehouse, the racks are transferred by the automated guided vehicles to the workstations. The contribution of the study is that it not only considers the optimal number of AGV but also the optimal number of workstation for automatic warehouse. To estimate the possible setting with the highest order turn-over rate, varies scenarios were considered in the model. As a result, the estimated layout and warehouse setting were suggested.